Hydroponic lettuce in-situ water circulation evaluation via nondestructive mass measurement in controlled environment - Huang, Yanhua; Ni, Zheng; Chang, Yanbin; Wang, Lizhi (Frontiers in Plant Science, 2024)
This study proposed a hydroponic system with the capacity to acquire high-resolution insitu mass data for non-destructive evaluation of water circulation in lettuce. The system customizes the watering profile, enables high-frequency in-situ weight measurement, and monitors multidimensional environment changes. Key air, water, and light parameters were collected to evaluate the plant response, susceptibility, and adaptability to environmental conditions. Multiple physiological indices were defined to characterize the properties of two lettuce varieties in response to different environmental factors.